Forest Brothers : The Account of an Anti-Soviet Lithuanian Freedom Fighter, 1944-1948 - Daumantas, Juozas, 1921-1951 (Book collections on Project MUSE., 2009)
"An autobigraphical account of the armed resistance movement against the Soviet Union which took place between 1944-1956. Published in English for the first time in unabridged form, Lukša's memoir remains one of the few reliable eye-witness accounts of the "Invisible Front" ... At its zenith 28,000 guerilla fighters participated in battles and skirmishes throughout Lithuania, Lukša being one of the leaders ... His account, written during 1948-1950 while he was living in hiding in Paris, describes in vivid scenes and dialogue the daily struggles of the resistance. Juozas Lukša ... [was] also known by code name Daumantas or Skirmantas"--Publisher's description